Art, Research, Philosophy - Cazeaux, Clive (Taylor & Francis, 2017)
The idea that art can be a form of research and, therefore, a contribution to knowledge, raises a number of philosophical questions such as: What is research in, through or for art? Should art draw upon research methods from other subjects, or develop its own? What kind of forms are produced or might be produced through artistic research?This is the first book to address the questions raised by visual arts research and is designed to give those working in the area new and challenging ways to reflect on how their practices engage with questions of knowledge-construction. Covering debates within aesthetics, epistemology and visual culture, this is an ideal text for art research students.